Photocatalytic oxidation of acetaminophen (ACT) using potassium peroxodisulfate (K2S2O8)-modified TiO2 photocatalyst - Aranzamendez, Graziel L. (College of Engineering, University of the Philippines Diliman, 2015)
Acetaminophen (ACT) is a globally prescribed analgesic and anti-inflammatory drug. In recent years, traces of unaltered ACT have been detected in conventional wastewater treatment effluent discharge. In this study, K2S2O8-modified TiO2 photocatalyst was synthesized and used to degrade ACT in aqueous solution under visible light irradiation. The effects of dopant amount, calcination temperature and calcination time on the properties and photocatalytic activity of the synthesizedcatalyst under visible light were investigated. Physical and chemical properties of the photocatalysts were analyzed using X-ray diffraction (XRD), Ultraviolet-visible light diffuse reflectance spectroscopy (UV- vis DRS), Brunauer-Emmett-Teller (BET) method, and X-ray photoelectron spectroscopy (XPS). K2S2O8-modified TiO2 having 0.50 wt % KaS2O8 as dopant and calcined at 300°C for 3 h removed 100% ACT with Kapp = 8.39 x 10-3 min-1. In the second phase of the study, effects of initial ACT concentration, catalyst dose, solution pH, and system temperature on the photocatalytic activity of K2S2O8-modified TiO2 were evaluated and the same batch reactor setup was utilized. After 9 h of reaction, 100% ACT degradation was achieved using 0.1 mM initial ACT concentration, catalyst dose of 2 g/L, initial pH of 9.0 and system temperature of 22°C (room temperature). The computed kapp for the reaction is equal to 7.29 x 10-3 min-1.